LIGHTWEIGHT AND MULTI-PURPOSE PARTITION FOR VERTICAL HOUSING - Eunike Kristi Julistiono; Lilianny Siegit Arifin; Bisatya Widadya Maer (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
Vertical housings have been developed to solve housing quality degradation due to rapid urbanization. These housings are often lack of privacy and comfort, since the lay-out mostly consists of one open plan space with limited area. This paper presents a lightweight and multi-purpose partition to improve the living quality in vertical housings. The lightweight characteristic is intended to minimize structural loads, while the multi-purpose property allows the partition to be transformed into some furniture for spatial efficiency. A literature review and material surveys were performed prior to material selection and the design process. Then, physical model experiments were carried out to simulate the installation process and the transformation process of the partition modules into some furniture. Result show that the partition’s weight is only 11-36.7% of the common partition wall, and when installed, the transformable property enables an adaptable space which can be adjusted to the occupants’ different conditions.